2014
DOI: 10.1002/adhm.201400291
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenylene Dendrimer Drug Transporter with Precisely Positioned Amphiphilic Surface Patches

Abstract: The design and synthesis of a polyphenylene dendrimer (PPD 3) with discrete binding sites for lipophilic guest molecules and characteristic surface patterns is presented. Its semi-rigidity in combination with a precise positioning of hydrophilic and hydrophobic groups at the periphery yields a refined architecture with lipophilic binding pockets that accommodate defined numbers of biologically relevant guest molecules such as fatty acids or the drug doxorubicin. The size, architecture, and surface textures all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 49 publications
2
48
0
1
Order By: Relevance
“…Finally, the dendrimers were prepared in moderate yields by a Diels-Alder reaction between 1,3,6,8-tetraethynylpyrene (1) and the CPs. Consequently, with the bromo-and iodo-functionalized CP 6 available, it is feasible to produce other functional materials including small molecules, dendrimers and polymers for versatile applications and fundamental research, such as dendrimers with hydrophilic and hydrophobic segments in the periphery as drug carriers into cells due to their amphiphilic solubility [44]. The crystal structure of the CAB-and PBD-functionalized CP 2 (Scheme 1) showed that the torsion angles between the central pentagon and phenyl groups at the 3,4-positions were 53° and 48° respectively due to the steric hindrance (see Figure S8).…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 99%
“…Finally, the dendrimers were prepared in moderate yields by a Diels-Alder reaction between 1,3,6,8-tetraethynylpyrene (1) and the CPs. Consequently, with the bromo-and iodo-functionalized CP 6 available, it is feasible to produce other functional materials including small molecules, dendrimers and polymers for versatile applications and fundamental research, such as dendrimers with hydrophilic and hydrophobic segments in the periphery as drug carriers into cells due to their amphiphilic solubility [44]. The crystal structure of the CAB-and PBD-functionalized CP 2 (Scheme 1) showed that the torsion angles between the central pentagon and phenyl groups at the 3,4-positions were 53° and 48° respectively due to the steric hindrance (see Figure S8).…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 99%
“…Organic synthesis allows us to tailor their properties for various biological purposes. 8 Clearly, dendrimers with combined hydrophobic/hydrophilic properties are of great interest as potential drug-delivery agents. (See ref 9 for a recent review.)…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this two‐chamber transwell system, bEND.3 and U‐87 MG cells were grown on the bottom of upper and lower chambers, respectively ( Figure A). The integrity of bEND.3 monolayer in vitro was evaluated by transendothelial electrical resistance . After the transendothelial electrical resistance value reached 200 Ω cm 2 , CARD‐B6 and CARD were added to the upper chamber, respectively.…”
Section: Resultsmentioning
confidence: 99%